Psychoeducation of Character Personal's Local Wisdom of Sundanese People's Behaviour in Internalizing Religious Commitment - Fenti Hikmawati (Universitas Islam Negeri (UIN), 2016)
Abstract This research aims to make new breakthroughs, to open the students' paradigm about psycho-education related to religious commitment as the internalization of the values ​​of the Sundanese Islam. Counseling method in this study used mixed methods with Triangulation A one-phased design models. Based on the analysis, it can be concluded that: (1) The students' increased commitment of religious is significant (47.37%) which is higher than the control group; (2) The answer of questionnaire item number one, two, and three in the experimental group is relatively balanced, with the emphasis on spoken and acted in number 23, whereas in the control group is relatively less balanced with emphasis on spoken and acted in number 13, and two who answered do not. Results of this study are expected to be an evaluation of the socialization of psychoeducation about the application of Islamic values ​​in the local policy on the vision and mission of the faculty, especially stakeholders. Abstrak Penelitian ini bertujuan untuk membuat terobosan baru dalam memberikan paradigma baru kepada mahasiswa tentang psiko-edukasi terkait dengan komitmen beragama sebagai internalisasi nilai-nilai Islam Sunda. Metode konseling pada penelitian ini menggunakan metode gabungan dengan model desain Triangulasi satu-fase. Berdasarkan analisis data, dapat disimpulkan bahwa: (1) Peningkatan komitmen relijius mahasiswa signifikan (47.37%) yang lebih tinggi daripada kelas kontrol; (2) Jawaban item angket nomor satu, dua, dan tiga pada kelas eksperimen cenderung seimbang dengan penekanan pada lisan dan tindakan di nomor 23, sedangkan di kelas kontrol cenderung tidak seimbang dengan penekanan pada lisan dan tindakan di nomor 13, dan dua orang menjawab tidak tahu. Hasil penelitian mengharapkan adanya evaluasi dari sosialisasi psiko-edukasi tentang penerapan nilai-nilai Islam peraturan lokalpada visi dan misi fakultas, khususnya pemangku kebijakan. How to Cite : Hikmawati, F. (2016). Psychoeducation of Character Personal's Local Wisdom of Sundanese People's Behaviour in Internalizing Religious Commitment. TARBIYA: Journal Of Education In Muslim Society, 3(1),  64-76. doi:10.15408/tjems.v3i1.3395. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v3i1. 3395